2017
DOI: 10.3390/en10111784
|View full text |Cite
|
Sign up to set email alerts
|

Wind Power Ramp Events Prediction with Hybrid Machine Learning Regression Techniques and Reanalysis Data

Abstract: Wind Power Ramp Events (WPREs) are large fluctuations of wind power in a short time interval, which lead to strong, undesirable variations in the electric power produced by a wind farm. Its accurate prediction is important in the effort of efficiently integrating wind energy in the electric system, without affecting considerably its stability, robustness and resilience. In this paper, we tackle the problem of predicting WPREs by applying Machine Learning (ML) regression techniques. Our approach consists of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…The estimation of the total power collected from wind turbines in a wind farm depends on several factors such as the location, hub height, and season. Cornejo-Bueno et al (2017) [98] applied different machine learning regression techniques to predict WPREs. Variables from atmospheric reanalysis data were used as predictive inputs for the learning machine.…”
Section: (A)mentioning
confidence: 99%
“…The estimation of the total power collected from wind turbines in a wind farm depends on several factors such as the location, hub height, and season. Cornejo-Bueno et al (2017) [98] applied different machine learning regression techniques to predict WPREs. Variables from atmospheric reanalysis data were used as predictive inputs for the learning machine.…”
Section: (A)mentioning
confidence: 99%
“…The proposed hybrid TSVR, RFR, and CNN methods are compared with SVM, 50 and ANN. 49 It is observed that TSVR and RFR models outperformed SVM and ANN models in terms of RMSE and other performance metrics. Further, in terms of computation speed, TSVR is observed to be the fastest among all models.…”
Section: Comparative Analysismentioning
confidence: 89%
“…5 that these two variables have a similar development trend qualitatively, which illustrates that the prediction errors contain the fluctuant elements related to wind power. To quantitatively calculate this correlation, formula (5) is utilised ρ e, P = 0.6037 (13) Result in (13) shows the correlation coefficient is inclined to 1, which illustrates that the prediction errors have a strong correlation with wind power, therefore we could further predict these system errors for correcting the original wind power prediction as (6) and (7).…”
Section: Wind Power Prediction By Model IImentioning
confidence: 99%
“…A probabilistic model using autoregressive logic model was proposed for ramp prediction [12]. Moreover, several machine learning regression models were applied for ramp prediction in literature [13]. While, inspection from the basic structure of event detection models, it is easy to see two directions require to be paid attentions on when studying for improving the performance of ramp prediction, such as preferable ramp detection algorithms and suitable wind power prediction models.…”
Section: Introductionmentioning
confidence: 99%